Securing the web - Oliver, Paul; Harding, Ben; Boland, Michael; Video Education Australasia (Australia : Video Education Australasia, 2006)
Takes a dramatic yet humorous look at current issues related to security and internet usage from the perspective of the end-user. Raises awareness of the importance of maintaining computer security and acting responsibly online. Focuses on both technological and behavioural solutions
Executive producer, Mark McAuliffe ; camera, Leigh Tilson ; editor, Paul Oliver
DVD format
Keywords: Computer networks -- Security measures; Computer security; Internet -- Security measures